Impact of Health Aid on Infant Mortality Rates - Ahmed Sadek Yousuf (The University of Nottingham, 2012)
This paper examines the relationship between health aid and infant mortality, using data from in total 135 countries, between 1975 and 2010. According to the findings, aid comes to have a statistically significant and positive effect on infant mortality rate, as doubling of aid leads to an approximately 1.3% reduction in infant mortality rates. Thus for an average aid recipient country, doubling per capita aid leads to a reduction of about 790 deaths per million live births in a particular year. This effect, in comparison to the set goals of the Millennium Development Goals, is small and may not be enough to ensure that the MDG targets are met by 2015.
Keywords: F35; C23; C33; I10; 300; Health Aid; Infant Mortality Rates; System GMM; Instrumental Variables; Public health insurance; Child mortality; Method of moments; Instrumental variables estimation